Unveiling the vital role of soil microorganisms in selenium cycling: a review - Jiang, Zhihui; Wang, Zhiyong; Zhao, Yong; Peng, Mu (Frontiers in Microbiology, 2024)
Selenium (Se) is a vital trace element integral to numerous biological processes in both plants and animals, with significant impacts on soil health and ecosystem stability. This review explores how soil microorganisms facilitate Se transformations through reduction, oxidation, methylation, and demethylation processes, thereby influencing the bioavailability and ecological functions of Se. The microbial reduction of Se compounds, particularly the conversion of selenate and selenite to elemental Se nanoparticles, enhances Se assimilation by plants and impacts soil productivity. Key microbial taxa, including bacteria such as Pseudomonas and Bacillus, exhibit diverse mechanisms for Se reduction and play a substantial role in the global Se cycle. Understanding these microbial processes is essential for advancing soil management practices and improving ecosystem health. This review underscores the intricate interactions between Se and soil microorganisms, emphasizing their significance in maintaining ecological balance and promoting sustainable agricultural practices.